miR-204-5p promotes the adipogenic differentiation of human adipose-derived mesenchymal stem cells by modulating DVL3 expression and suppressing Wnt/β-catenin signaling - HE, HONGHUI (Int J Mol Med, 2015)
MicroRNAs (miRNAs or miRs) play an important regulatory role during adipogenesis, and have been studied extensively in this regard. Specifically, the switch between the differentiation of mesenchymal stem cells (MSCs) towards adipogenic vs. osteogenic lineages is regulated by miR-204 which controls the expression of Runx2. However, the association between miR-204-5p and the Wnt/β-catenin signaling pathway during adipogenesis has not yet been clarified. In the present study, we demonstrate that miR-204-5p regulates the in vitro adipogenesis of human adipose-derived mesenchymal stem cells (hADSCs). The level of miR-204-5p was shown to be gradually upregulated during adipocytic differentiation, together with the mRNA expression of the critical adipogenic transcription factors, cytidine-cytidine-adenosine-adenosine-thymidine (CCAAT) enhancer binding protein α (C/EBPα) and peroxisome proliferator-activated receptor γ (PPARγ), and the mature adipogenic marker, fatty acid binding protein 4 (FABP4). We further demonstrate that while the overexpression of miR-204-5p promotes adipogenesis, its knockdown causes the inhibition of this process. We then used bioinformatics tools and luciferase reporter assay to establish that dishevelled segment polarity protein 3 (DVL3), a key regulator of the Wnt/β-catenin signaling pathway, is a direct target of miR-204-5p. In addition, the overexpression of DVL3 led to an increase in β-catenin and cyclin D1 (CCND1) expression and, by contrast, the knockdown of DVL3 led to a decrease in the expression of β-catenin and CCND1. The knockdown of DVL3 significantly promoted adipogenesis. Finally, we demonstrated that the overexpression of miR-204-5p induced the downregulation of β-catenin and the canonical Wnt target gene, CCND1, in mature adipoctyes, while its knockdown led to their upregulation. Taken together, our data suggest that miR-204-5p regulates adipogenesis by controlling DVL3 expression and subsequently inhibiting the activation of the Wnt/β-catenin signaling pathway.